Bridging Languages: Impact of Translanguaging on Indonesian ELT Through Teachers’ and Students’ Perspectives - Kausch II, Christoper J.; Safriani, Afida; Aldianto, Aldianto (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
The growing prominence of translanguaging has significantly influenced English Language Teaching (ELT) in classrooms over the past few decades. As a pedagogical tool, translanguaging can support teachers in facilitating ELT. However, its application in an English as a Foreign Language (EFL) context is often met with skepticism. This research seeks to explore teachers’ and students’ perspectives on the use of translanguaging as a pedagogical tool to enhance ELT in Indonesia. Employing a case study approach, the study gathered in-depth insights through Focus Group Discussions (FGDs) and interviews with ten students and six teachers from SMPN 1 Buduran and MTsN 2 Sidoarjo. The findings highlight that teachers view translanguaging as a valuable tool for scaffolding concept explanations, boosting student engagement and communication, managing classrooms, supporting learners with lower English proficiency, and creating a more comfortable and supportive learning environment. Similarly, students perceive translanguaging as a helpful strategy to improve their understanding of lesson content, facilitate peer communication, and build confidence in expressing their ideas. The study contributes to the growing body of research on translanguaging by offering empirical evidence from the Indonesian EFL context, underscoring its potential to bridge linguistic gaps and promote more inclusive, effective English language instruction.